ANALISIS TATANIAGA KAMBING DI PASAR HEWAN WLINGI KABUPATEN BLITAR - M. Zainul Infanda (AVES: Jurnal Ilmu Peternakan, 2017)
At the process trade of goat in Blitar, esspecially in animal market “Terpadu-- Wlingi that is “pasaran-- (in Indonesia) Tuesday, Thrusday, and Saturday and also there is some channel of trade, and kinds of cost that issued efery channel.This research to know groove of trading goat and farmer ’s share in Blitar especiaally animal market “terpadu-- Wlingi. Method of research that used is survey, used sunaple more that 10 traders that experienced of trader minimal 5 years. Result of research to show that there is marketing that “blantik--, breeder, customer, and grocier big. Margin of marketing higher is Rp 750.000 efery goat. Farmer ’s share that received breeder higher that first channel (breeder-costumer) is 100%. The channel of marketing that first channel is so eficient. Cost and margin a lowest at first channel. Farmer ’s share is lowest at third channel. Channel of marketing at first channel more eficientli because it has done Farmer ’s share more higher is 100%.Keywords: Goat, Commerce, Wlingi Blitar.